2015
DOI: 10.1097/jcp.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment Outcome in Adult Male Prisoners With Attention-Deficit/Hyperactivity Disorder

Abstract: Despite high rates of attention-deficit/hyperactivity disorder (ADHD) among adult lawbreakers, particularly the long-term effects of ADHD pharmacotherapy remain unclear, not the least because of ethical challenges with preventing control subjects in randomized controlled trials from receiving medication over prolonged time. We followed up adult male prisoners with ADHD who completed a 5-week randomized, double-blind, placebo-controlled trial followed by a 47-week open-label extension of osmotic-release oral sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 36 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Longer-term follow-ups, though not directly addressing crime outcomes, failed to find significant clinical differences after 10 years (Secher et al, 2014). Ginsberg et al (2015) report on the impact of an experimental evaluation of the effects of methylphenidate, a pharmacological treatment for Attention-Deficit/Hyperactivity Disorder (ADHD), on adult male prisoners in a maximum security Swedish prison. The study design included a 5-week randomized, double-blind, placebo-controlled trial followed by a 47-week extension during which all participants received oral methylphenidate (see also Ginsberg and Lindefors, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer-term follow-ups, though not directly addressing crime outcomes, failed to find significant clinical differences after 10 years (Secher et al, 2014). Ginsberg et al (2015) report on the impact of an experimental evaluation of the effects of methylphenidate, a pharmacological treatment for Attention-Deficit/Hyperactivity Disorder (ADHD), on adult male prisoners in a maximum security Swedish prison. The study design included a 5-week randomized, double-blind, placebo-controlled trial followed by a 47-week extension during which all participants received oral methylphenidate (see also Ginsberg and Lindefors, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, we have observed a tentative embrace of random assignment and experimental analyses, even in complex correctional environments and among challenging populations. For example, Ginsberg and colleagues (2015) were able to conduct a 52-week ADHD medical trial in a Swedish maximum security prison, and rehabilitative programming has also been randomly allocated to inmates throughout Scandinavia (for example, Berman, 2004; Forsberg et al, 2011; Gold et al, 2014). Although none of these RCTs included a crime-related outcome, and hence are excluded from this systematic review, there is little reason to suggest that simply including these outcomes would pose additional implementation challenges.…”
Section: Conducting Randomized Experiments: Institutional and Culturamentioning
confidence: 99%
“…The most common pharmacological treatment is stimulant-medication (55). The latter has been shown to prevent risk-behavior such as criminality (56). …”
Section: Executive Functioning Problems and Adhdmentioning
confidence: 99%
“…Difficulties in the domains of attention, hyperactivity, and impulsivity are present across adult forensic and forensic psychiatric populations at both clinical (i.e., attention deficit hyperactivity disorder, ADHD) and subclinical levels (1, 2). A meta-analysis by Young et al (3) indicated that 31% of adult prisoners meet criteria for ADHD, compared to 2.5–4.2% in community adult populations.…”
Section: Introductionmentioning
confidence: 99%